Durability study on engineered cementitious composites (ECC) under sulfate and chloride environment. (15th February 2017) - Liu, Hezhi; Zhang, Qian; Li, Victor; Su, Huaizhi; Gu, Chongshi
Highlights: ECC remains durable after 200 days of exposure to sulfate and sulfate-chloride environment. Long-term exposure leads to compressive and tensile strength increase of ECC. Long-term exposure leads to slight reduction of tensile strain capacity of ECC. Composite level behavior of ECC is a result of changed matrix fracture toughness and fiber/matrix interfacial bond. Tensile ductility reduction of ECC is attributed to reduced crack number and width. Abstract: The lack of durability of concrete hydraulic structures, especially under sulfate and chloride environment, has become a worldwide problem. The present paper investigated the feasibility of applying ductile engineered cementitious composites (ECC) as an alternative to conventional concrete in hydraulic structures to improve their durability performance. Specifically, the durability of ECC under sulfate and combined sulfate-chloride conditions were studied. Compressive and tensile behavior of ECC after long-term exposure to Na2 SO4 and Na2 SO4 + NaCl solutions was experimentally characterized. Subsequently, micromechanical study was adopted to investigate the microscopic mechanisms underlying the composite level behavior of ECC under those aggressive environments. The research findings demonstrated that ECC remains durable and maintains its high mechanical performance even after 200 days of exposure to concentrated sulfate and combined sulfate-chloride environments. In addition, the micromechanics-based study quantitatively characterized the influence of sulfate and sulfate-chloride solutions on the micromechanical parameters including matrix fracture toughness and fiber/matrix interfacial bond, providing insights into the underlying mechanisms of the composite level behavior of ECC under those environments.